The effect of the SM2CL learning model on students’ critical thinking skills in the digestive system topic - Pratama, Lisra; Taiyeb, Mushawwir; Rachmawaty, Rachmawaty; Daud, Firdaus; Mu’nisa, Andi (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
The demands of 21st-century education emphasize critical thinking in learning. Critical thinking is essential in learning biology, especially in the topic of the human digestive system. However, the limited use of varied learning models reduces opportunities to develop students' critical thinking skills. Therefore, an appropriate learning model is needed, namely the SM2CL model. This model is appropriate because it combines learning models, strategies, and methods. This study aims to analyze the effect of the Synectics, Mind Mapping, and Cooperative Learning (SM2CL) learning model on critical thinking skills among class XI students in the digestive system material at MAN 3 Bone. This study used a quasi-experimental method with a pretest-posttest control group design. The study consisted of 60 samples, comprising 2 classes of students. The study, using ANCOVA to test the hypothesis, showed a significant effect of the SM2CL model (p < 0.05). Furthermore, the LSD test indicated a significant difference between students taught using the SM2CL model and those taught using the direct instruction model. These findings suggest that the SM2CL model is more effective in enhancing students' critical thinking skills in biology learning, particularly in the digestive system topic. This study contributes to biology education by providing empirical evidence on the effectiveness of integrated learning models in promoting critical thinking skills.Abstrak. Tuntutan pendidikan abad ke-21 menekankan pemikiran kritis dalam pembelajaran. Pemikiran kritis sangat penting dalam pembelajaran biologi, khususnya pada topik sistem pencernaan manusia. Namun, penggunaan model pembelajaran yang beragam yang terbatas mengurangi kesempatan untuk mengembangkan kemampuan berpikir kritis siswa. Oleh karena itu, dibutuhkan model pembelajaran yang tepat yaitu model SM2CL. Model ini tepat karena memadukan model, strategi dan metode pembelajaran Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Synectics, Mind Mapping, dan Cooperative Learning (SM2CL) terhadap kemampuan berpikir kritis siswa kelas XI pada materi sistem pencernaan di MAN 3 Bone. Penelitian ini menggunakan metode quasi-eksperimental dengan desain kelompok kontrol pretest-posttest. Penelitian ini terdiri dari 60 sampel yang terdiri dari dua kelas siswa. Hasil penelitian, menggunakan uji ANCOVA untuk menguji hipotesis, menunjukkan pengaruh signifikan model SM2CL dengan nilai signifikansi p < 0,05. Selanjutnya, uji LSD menunjukkan perbedaan signifikan antara siswa yang diajar menggunakan model SM2CL dan siswa yang diajar menggunakan model pengajaran langsung. Temuan ini menunjukkan bahwa model SM2CL lebih efektif dalam meningkatkan kemampuan berpikir kritis siswa dalam pembelajaran biologi, khususnya pada topik sistem pencernaan. Studi ini berkontribusi pada pendidikan biologi dengan memberikan bukti empiris tentang efektivitas model pembelajaran terintegrasi dalam meningkatkan kemampuan berpikir kritis.